Mapping the Evolution of Corporate Social Responsibility Research (2015–2024): A Bibliometric Analysis Based on Scopus - Cristyano Cristyano; Suryadi Suryadi; Riyanto Riyanto (Universitas Muhammadiyah Yogyakarta, 2025)
This study presents a comprehensive bibliometric analysis of Corporate Social Responsibility (CSR) research published between 2015 and 2024, drawing on 624 articles indexed in the Scopus database. The objective is to map the intellectual evolution of CSR scholarship by identifying key thematic shifts, dominant theoretical frameworks, and methodological patterns. Using VOSviewer as the primary visualization tool, the study explores research networks, keyword co-occurrences, and temporal transitions in CSR literature over the past decade. The analysis reveals a notable progression in CSR themes, moving from early emphases on business ethics and corporate governance toward sustainability, stakeholder engagement, ESG integration, and digital transformation. Stakeholder Theory, Legitimacy Theory, and Institutional Theory emerge as the most influential conceptual foundations, shaping both normative debates and strategic implementation. While quantitative approaches continue to dominate, the growing adoption of qualitative and mixed-method designs reflects a deeper inquiry into CSR’s societal relevance and ethical dimensions. Geographically, CSR research remains concentrated in developed countries such as the United States, China, the United Kingdom, and Australia, although contributions from emerging economies are steadily increasing. Despite the expansion of the field, gaps persist in the standardization of CSR metrics and in evaluating its long-term social impacts beyond corporate financial performance. The novelty of this study lies in its integration of bibliometric mapping with theoretical synthesis to provide a holistic, data-driven perspective on the evolution of CSR research over the past decade, offering fresh insights into future research directions aligned with sustainable development, inclusive governance, and cross-sector collaboration.